2006
DOI: 10.1253/circj.70.1525
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Obesity to Acute Myocardial Infarction in Japanese Patients Differences in Gender and Age

Abstract: besity is a risk factor for coronary heart disease (CHD) among adults 1 and is increasing in prevalence among young adults, as well as adults. 2,3 A recent report indicated a significant association of obesity with coronary atherosclerosis in young male adults, particularly in those with a central pattern of adiposity, and little association of obesity with coronary atherosclerosis in young female adults. 4 Still another recent report points out that adiposity and its metabolic disturbances (ie, metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Previous studies reported that obesity and low HDL cholesterolemia were independent risk factors among younger male patients [33][34][35] , which is consistent with our findings. In particular, male patients with AMI aged 40 years showed significant increases in BMI and the prevalence of obesity (Fig.…”
Section: Changes In the Prevalence Of Coronary Risk Factors In Ami Pasupporting
confidence: 93%
“…Previous studies reported that obesity and low HDL cholesterolemia were independent risk factors among younger male patients [33][34][35] , which is consistent with our findings. In particular, male patients with AMI aged 40 years showed significant increases in BMI and the prevalence of obesity (Fig.…”
Section: Changes In the Prevalence Of Coronary Risk Factors In Ami Pasupporting
confidence: 93%
“…These findings agree with other studies of Chinese and other Asian populations, documenting linear relations of BMI or waist circumference with cardiovascular disease risk factors. 5,6,10,[13][14][15][16] Moreover, based on the sensitivity, specificity and ROC calculations, our data suggest a BMI of 24 kg/m 2 for both men and women, and a waist circumference of 85 cm for men and 80 cm for women as appropriate cut-off values for the designation of overweight and central adiposity in this population.…”
Section: Discussionmentioning
confidence: 60%
“…Hayashi et al recommended an age-specific assessment of VFA when evaluating obesity-related cardiovascular risk factors in females 32) . Other studies have also confirmed increases in cardiovascular events and thr frequency of metabolic risk factors after menopause 33,34) . Taken together, it is possible that the female subjects in the present study were too young to assess the effect of visceral fat on the number of metabolic risk factors.…”
Section: Discussionmentioning
confidence: 76%